Finding and evaluating evidence systematic reviews and evidence-based practice - Bronson, Denise E.; Davis, Tamara S. (New York ; Oxford : Oxford University Press, 2011)
This pocket guide is an introduction to evidence-based practice systematic reviews, and meta-analysis for social work students practitioners, and scholars. It provides a concise overview of how to complete a systematic review and criteria for assessing the quality of existing reviews.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social service -- Research; Evidence-based social work